Psychological work immersion enablers and behavioural indicators: Exploring socio-demographic differences among staff members - Coetzee, Melinde; Veldsman, Dieter (African Journal of Employee Relations, 2019)
Research on surface-level diversity pertaining to differences among gender, age, race and tenure groups regarding their psychological work immersion has been limited in the South African organisational context. The present study explored whether gender, age, race and tenure groups differ significantly in terms of their perceptions of organisational enablers and behavioural indicators of employee engagement as measured by the psychological work immersion scale. The sample was a non-probability sample (N = 1 268) of individuals employed across various South African industries. The sample was predominantly made up of females (74%) and black people (86%) in the early (49%: 21–35 years) and establishment (51%: 36–50 years) career phases. Most individuals in the sample had less than five years of work experience (69%). Tests for independent samples revealed significant differences among the biographical groups on the psychological work immersion enabler and behavioural indicator variables. The results indicated that surface-level diversity characteristics are important to consider in strengthening employees’ work immersion as an aspect of employment relations. The differences observed provide valuable insights that could potentially be used by management in the design of business performance and retention strategies.